29th Divisional Artillery : War Record and Honours Book 1915-1918. - Johnson, R. M. (Andrews UK, 2012)
The 29th Division ("The Incomparable 29th") was formed between January and March 1915 and took part in the Gallipoli campaign from the landings in April 1915 till evacuated in January 1916, and then went to the Western Front where it remained for the rest of the war. In all it won twenty-three VCs, the highest number awarded to any division, one of them to Capt Walford of the divisional artillery. This record originated in the Honours Book kept by 29th Division's GOC, Maj-Gen de Lisle (June ...